Correlates of Presence and Remission of Post-trauma Stress Disorder in Incarcerated Women: A Case-Control Study Design - Zhong, Shaoling; Zhu, Xiaomin; Mellsop, Graham; Zhou, Jiansong; Wang, Xiaoping (Frontiers in Psychiatry, 2021)
Women in prison are vulnerable to post-trauma stress disorder (PTSD). However, little is known about the presence of PTSD in imprisoned women or of the natural course of that disorder. The purpose of this study was to assess the risk factors for PTSD in incarcerated women and document correlations of remission. We conducted a retrospective case-control study in the Female Prison of Hunan Province, China. Participants were screened for PTSD and depression using the Chinese version of the MINI International Neuropsychiatric Interview (MINI) 5.0. Of the 2322 screened 220 met the criterion for PTSD on admission. Remission (N=142) and non-remission PTSD (N=78) were then separated depending on current PTSD status. History of drug use (OR=0.43, 95%CI: 0.28-0.66, p<.001) and violent offense (OR=1.56, 95%CI: 1.17-2.09, p<.001) were associated with the presence of PTSD. Positive associations with remission were found for longer length of sentence (61-120 months vs. 13-60 months) (OR=4.20, 95%CI:1.50-11.75, p=.006), violent offense (OR=2.50, 95%CI:1.12-5.60, p=.03) and comorbid depression (OR=29.69, 95%CI:3.50-251.78, p=.002); while a negative correlate was identified for past depression (OR=0.24, 95%CI:0.11-0.53, p<.001). Although some incarcerated women with PTSD can spontaneously remit, this study suggested certain criminological and clinical risk factors are associated with the presence of PTSD and others with remission over time. Timely screening and effective intervention should be tailored for individuals with PTSD in prisons.